2010
DOI: 10.1086/649878
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis and Food‐Borne Disease in Elderly People Living in Long‐Term Care

Abstract: Elderly people in long-term care facilities (LTCFs) may be more vulnerable to infectious gastroenteritis and food-borne disease and more likely to experience serious outcomes. We review the epidemiology of gastroenteritis and food-borne diseases in elderly residents of LTCFs to inform measures aimed at preventing sporadic disease and outbreaks. Gastroenteritis in elderly people is primarily acquired from other infected persons and contaminated foods, although infections may also be acquired when residents have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 85 publications
1
35
0
Order By: Relevance
“…Although clinicians might elect not to collect specimens when LTCF residents have diarrheal illness, we think it more likely that reporting is more complete in LTCFs. Most of the diseases in our study are serious illnesses, and infected persons would have severe gastrointestinal and extraintestinal symptoms lasting for several days or weeks ( 3 , 4 ). In a case–control study of campylobacteriosis in Australia, 41% of case-patients had bloody diarrhea, and 75% had fever; both of these symptoms are strong predictors for physicians ordering laboratory tests ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although clinicians might elect not to collect specimens when LTCF residents have diarrheal illness, we think it more likely that reporting is more complete in LTCFs. Most of the diseases in our study are serious illnesses, and infected persons would have severe gastrointestinal and extraintestinal symptoms lasting for several days or weeks ( 3 , 4 ). In a case–control study of campylobacteriosis in Australia, 41% of case-patients had bloody diarrhea, and 75% had fever; both of these symptoms are strong predictors for physicians ordering laboratory tests ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CFRs were consistent with reports in the literature for elderly persons, although we assessed deaths only short term (i.e., in the weeks after infection) ( 34 , 35 ). In general, elderly persons have more severe outcomes from foodborne infections than do younger persons ( 4 , 18 ). Large-scale studies that used population-based registers have demonstrated that enteric diseases contribute to more deaths than recognized from short-term follow-up, even when controlling for concurrent conditions ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, elderly patients are known to be especially susceptible to Salmonella gastroenteritis (31). Those in long-term-care facilities are particularly vulnerable, with a casefatality rate up to 70 times greater than the general population (32,33). As such, a vaccine that could protect this population specifically is also desirable.…”
Section: Salmonella Vaccinesmentioning
confidence: 99%